International Tourist Satisfaction towards tourism activities and facilities: A case study in Mamutik Island, Kota Kinabalu, Sabah, East Malaysia / Velan Kunjuraman ... [et al.] - Kunjuraman, Velan; Hussin, Rosazman; Ahmad, Abdul Rahman (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2015)
The main objective of this study is to identify international tourist satisfaction towards tourism activities and tourist facilities in Mamutik Island, Kota Kinabalu, Sabah. Mamutik Island is located in the Tunku Abdul Rahman Marine Park and it can be reached in 20 minutes by boat from Jesselton Point, Kota Kinabalu City. The main tourist activities of Mamutik Island are scuba diving, snorkelling, swimming and marine lives observing. There are various tourist services and facilities provided by the Island management such as jetty, toilet, picnic and barbeque area, sun bathing kits and stalls. However, study on international tourist satisfaction towards these activities and facilities on this island were limited. Therefore, a survey method through questionnaire was applied in this study. There were two sets of questionnaires used for data collection in English and Mandarin languages. A total number of 150 international tourists were surveyed in this study. The findings indicate that majority of the international tourists are satisfied with the tourist activities and facilities of the island. However, there are certain aspects that should be considered by the management in order to increase the level of international tourist satisfaction such as to increase number of toilet and facilities, interesting tourist activities and provide scuba diving equipment at reasonable prices. Thus, this study is significant to indicate how the distinctiveness of tourist activities and quality of facilities can ensure international tourist loyalty to revisit tourist destinations in Sabah.